The Stakeholders Engagement Study in Rural Development Program - Santosa, Fajar Julian; Setyowati, Retno; Wibowo, Agung (JRCE (Journal of Research on Community Engagement), 2024)
Rural development is integral to achieving sustainable development in Indonesia, where success is measured from an economic, social, and environmental perspective. As a region with cultural riches and abundant natural resources, the Special Region of Yogyakarta has become a focal point in village development efforts. One example of successful village development is in Kulwaru Village, where communal cattle were constructed. This research aims to explore the role and engagement of stakeholders in village development in the case of communal cattle. This study uses a qualitative case study method by collecting data through in-depth interviews with 15 informants, including local government, group leaders, community leaders, community organizations, and other related organizations. The data was then analyzed descriptively, and a power and interest matrix was used to determine the role positions of the stakeholders. This research found that stakeholder engagement has different powers and interests. Stakeholders included in the categories (1) Key players: administrators, livestock group members, and BKM Bina Mandiri; (2) Keep Informed: Kubaweta Cooperative, Puskeswan, IAAS UGM, and Academics. (3) Keep Satisfied: Kulwaru Village Government, District Agriculture and Food Service. Kulon Progo, the Central and Provincial PUPR Ministries; and (4) monitor category, the PUPR District Service. Kulon Progo. Collaboration between these stakeholders plays a vital role in the success of building communal cattle and surviving and overcoming the slum environment problems faced by the people of Kulwaru Village.